Pomerania (Over)drawn: The Poetics of the Historic and the Local in the World of Comics - Kalinowski, Daniel (Porównania, 2021)
The text concerns the description of contemporary phenomena of a comic created in Pomerania and about Pomerania. The basis for the analysis was the two-volume Komiks szczeciński publishing house of various authors from the capital of the West Pomeranian Voivodeship, Wojciech Stefaniec’s Opowieści znad Bałtyku, Szczęściarz z rocznika 1917 by Agnieszka Kosko-Hołowczyc and Wanda Swajda, as well as two Kashubian comic books Szczenię Swiãców and Arbata, written by Piotr Dziekanowski. The combination of comics from various Pomeranian subregions and different genres of artists shows, with all appreciation of the tendency to originality, a puzzling similarity in creating images of culturally important places. These analogies can be considered by designating several categories of comic poetics: historicism and locality. In addition to the issue of poetics, there is also the question of the social need for a new creation of “magical” places of the regional landscape, to which the modern comic book movement responds.